Symposium Wrap-Up: What is Missing? - Robert J. Robel (National Quail Symposium Proceedings, 2017)
The program committee requested that I provide a symposium wrap-up. Generally such presentations provide 1 individual the opportunity to summarize and integrate the information presented during the meeting. That overview is often helpful, if there are several concurrent sessions or if most of the attendees spend their time interacting in the hallways and, thus, miss some of the presentations. Also, the wrap-up speaker can congratulate the organizers of the meeting for a job well done. I intend to neither summarize the information presented nor thank the organizers for doing a good job. Neither of these is necessary, because you all attended the majority of presentations and can summarize and integrate the data in your own head; the fact that the sessions were so well attended attests to an extremely good job done by the organizing committee. So, rather than doing what is not necessary, I intend to discuss what was missing in this symposium, the problems that were not addressed in the papers, and the data gaps that must be filled if we are to successfully manage quail populations in North America. From my perspective, these fall into 6 categories.